Pulmonary rehabilitation for post-TB lung disease led by TB survivors - F.J. Mtei; I. Meadows; K. Msaji; F. Thobias; A. Liyoyo; A. Kimaro; P.M. Joseph; C. Gitige; O. Kaswaga; S. Matoi; A. Ngoma; A. Mbuya; et al. (Public Health Action)
BACKGROUND: Post-TB patients often experience persistent lung issues that impair exercise capacity and quality of life. Although pulmonary rehabilitation is known to be effective for chronic lung diseases, its role in post-TB lung disease remains underexplored in high TB-burden settings. METHOD: This prospective study (2021–2022) in Tanzania's Kilimanjaro region evaluated a 24-week, community-based pulmonary rehabilitation program led by TB survivors for adults with moderate-to-severe respiratory symptoms despite TB cure. The program included supervised exercise, breathing training, psychosocial support and smoking cessation. Outcomes measured at baseline, 12 weeks, and 24 weeks included spirometry, 6-minute walk distance (6MWD), St. George’s Respiratory Questionnaire (SGRQ), BMI, Generalized Anxiety Disorder-7 (GAD-7), and Patient Health Questionnaire-9 (PHQ-9). RESULTS: Among 121 participants (mean age 48±8.67 years, 89.2% male), significant improvements were observed in 6MWD (420 vs. 460 meters, p < 0.001) and SGRQ scores (34.63 to 12.99, p < 0.001). Smoking history predicted SGRQ improvement. Although no changes were seen in lung function or BMI, anxiety and depression symptoms improved in those with abnormal baseline scores. CONCLUSION: Community-based pulmonary rehabilitation improved symptomatic individuals' quality of life, physical capacity and mental health. Future research should refine intervention timing and evaluate long-term outcomes across diverse settings.